Beginning of “Kulak Exile” to the Tobolsk North (1930) - L. V. Alekseeva (Научный диалог, 2020)
The article contains systematic information about the process of resettlement of dispossessed peasants to the North of Western Siberia during the 1930s. It is alleged that this was the first stage of peasant exile, which began in February 1930. In total, researchers distinguish three stages (1930-1933). Based on documents and scientific publications, plans for the resettlement of dispossessed peasants to the Tobolsk North is discussed in the article. Features of preparation for the resettlement of “kulaks” and members of their families to the North by the example of agricultural districts of the Ural region are disclosed. The novelty of the study is that the author by comparative analysis reveals the number of peasants to be evicted, as well as the number of peasants who appeared in the Tobolsk north by the end of 1930. Particular attention is paid to the processes of transporting “kulaks” in two stages: in winter, and also in spring et summer (in navigation) in 1930. For the first time, data on the number of peasants delivered by river transport to the North is presented. The names of steamboats, the number of barges that transported people, places of settlement are reported. Statistics on the ratio of the number of local population and special settlers in the Yamalo-Nenets and Khanty-Mansiysk districts is provided. Digital data allow the author to conclude that the North of Western Siberia has become a region of increased concentration of special groups of population.